Life aspirations, school engagement, social anxiety, social media use and fear of missing out among adolescents - Tanrikulu, Gulfem; Mouratidis, Athanasios (Current Psychology, 2022)
Fear of Missing Out (FoMO) – people’s intense concerns that they might miss pleasant moments that their peers may enjoy—has been found to relate to a variety of undesired outcomes, including poor academic functioning. Yet, little is known about why some students may exhibit more FoMO than others. In this cross-sectional study with a sample of Turkish adolescents (N1 = 506; 50.8% males; Mage = 15.8 years; SD = 0.83), we examined to what extent intrinsic and extrinsic life goals for using social media predict FoMO over and above social anxiety. We found through path analyses that extrinsic goals of attaining popularity, garnering attention, and conveying a positive image of oneself to others related to FoMO which in turn related to lower grades by means of in-class distraction and out-of-class study interference. Taken together, the present results suggest that the goals that adolescents try to attain through social media use may explain why FoMO might be more prevalent in that age group.